2004
DOI: 10.1136/jme.2003.005389
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of healthcare professionals and parents regarding genetic testing for violent traits in childhood

Abstract: Objectives: Although no genetic tests for violent behaviour are currently available, research is ongoing to isolate genes related to a propensity for violence. We explored the attitudes of parents and healthcare professionals toward behavioural genetic testing for violence. Design: The attitudes of healthcare professionals and the lay public about genetic testing of children were elicited for a range of conditions through interviews with healthcare professionals and focus groups with parents. All participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 27 publications
0
24
1
Order By: Relevance
“…Milner et al's (1999) survey of Michigan psychiatrists and psychiatric residents found that most supported the availability of prenatal testing for susceptibility to severe mental illness. Contrary findings were reported in Campbell and Ross (2004) interview study of genetic professionals and pediatricians about the hypothetical testing of children for genes conferring a propensity toward violence. Most of the health care professionals polled by these investigators would advise against such testing unless treatment were available.…”
Section: Positive Attitudes Toward Genetic Testingcontrasting
confidence: 62%
“…Milner et al's (1999) survey of Michigan psychiatrists and psychiatric residents found that most supported the availability of prenatal testing for susceptibility to severe mental illness. Contrary findings were reported in Campbell and Ross (2004) interview study of genetic professionals and pediatricians about the hypothetical testing of children for genes conferring a propensity toward violence. Most of the health care professionals polled by these investigators would advise against such testing unless treatment were available.…”
Section: Positive Attitudes Toward Genetic Testingcontrasting
confidence: 62%
“…This concern may be greatest for genetic risks related to psychiatric problems or undesirable behaviors. 24 An example illustrates some of the questions raised by behavioral genetic studies. A prospective follow-up of a birth cohort initially enrolled at 3 years of age most recently reported follow-up at 26 years of age, when a DNA sample was collected for genetic studies.…”
Section: Personal and Group Stigmamentioning
confidence: 99%
“…In focus groups involving minority parents, for example, participants expressed the fear that a genetic test to identify persons with a genetic susceptibility toward violent behavior would more likely be used in black youth than in white youth. 24 These concerns reflect a long history of the use of questionable biological explanations for behaviors and health problems that are prevalent in minority populations, despite apparent socioeconomic causes. 29, 30 Cooper 31 argues that "minority groups, particularly blacks in the United States, are assumed to be genetically predisposed to virtually all common chronic diseases.…”
Section: Personal and Group Stigmamentioning
confidence: 99%
“…Similarly, couples at high-risk for genetic disease in their children favor legislation that permits the use of PGD [9] and are more likely to believe that offering PGD is considered ethical practice [10]. While there are limited studies on the attitudes of the general population, it seems that medical professionals may have more negative views towards genetic tests [11,12].…”
Section: Introductionmentioning
confidence: 99%